Cytokines and chemokines: The vital role they play in herpes simplex virus mucosal immunology - Smith, Jacinta B.; Herbert, Jason J.; Truong, Naomi R.; Cunningham, Anthony L. (Frontiers in Immunology, 2022)
Herpes simplex viruses (HSV) types 1 and 2 are ubiquitous infections in humans. They cause orofacial and genital herpes with occasional severe complications. HSV2 also predisposes individuals to infection with HIV. There is currently no vaccine or immunotherapy for these diseases. Understanding the immunopathogenesis of HSV infections is essential to progress towards these goals. Both HSV viruses result in initial infections in two major sites - in the skin or mucosa, either after initial infection or recurrence, and in the dorsal root or trigeminal ganglia where the viruses establish latency. HSV1 can also cause recurrent infection in the eye. At all of these sites immune cells respond to control infection. T cells and resident dendritic cells (DCs) in the skin/mucosa and around reactivating neurons in the ganglia, as well as keratinocytes in the skin and mucosa, are major sources of cytokines and chemokines. Cytokines such as the type I and II interferons synergies in their local antiviral effects. Chemokines such as CCL2, 3 and 4 are found in lesion vesicle fluid, but their exact role in determining the interactions between epidermal and dermal DCs and with resident memory and infiltrating CD4 and CD8 T cells in the skin/mucosa is unclear. Even less is known about these mechanisms in the ganglia. Here we review the data on known sources and actions of these cytokines and chemokines at cellular and tissue level and indicate their potential for preventative and therapeutic interventions.